Choosing a life work - Taft, Edwin S. (My University, 1908)
Introduction: It has been said that, since vocation is the chief support of the home and tends to develop individual character and manhood, just so it clearly underlies the welfare and prosperity of the nation.
Citation: Taft, Edwin S. Choosing a life work. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Men; Life; Work; Education; Graduating theses; Senior theses; Theses